VISI PENDIDIKAN ISLAM: PERSPEKTIF IBN KHALDUN - Saepudin, Didin; Saifudin, Saifudin (Tawazun: Jurnal Pendidikan Islam, 2019)
The purpose of this study is to find out the vision of Islamic education from Ibn Khaldun's perspective. This research is a qualitative research. The methodology and approach used are content analysis. The main source of research is the work of Ibn Khaldun Muqaddimah Ibn Khaldun. This article concludes that the vision of Islamic education according to Ibn Khaldun is to form talented Muslim personalities, both intellectual and personality (moral / moral) talents. In addition, in order for him to be competent in the life of Islamic education, he must also have a pragmatic goal, which is to provide skills relevant to the demands of the times. With these talents one will be able to realize the civilization (‘umran) of the world and prosper it. Such purpose is in harmony with the function of human creation as khalifah on earth. When every human being is able to become a khalifah in the true sense, he will be a mercy for the universe (rahmatan lil ‘lamí®n) as is the role of the Prophet Muhammad as a prophet for all people. Abstrak Tujuan penelitian ini adalah mengetahui visi pendidikan Islam perspektif Ibn Khaldun. penelitian ini merupakan penelitian kualitatif. Metodologi dan pendekatan yang digunakan adalah analisis isi (content analyzis). Sumber utama penelitian adalah karya Ibn Khaldun: Muqaddimah Ibn Khaldun. Artikel ini menyimpulkan bahwa visi pendidikan Islam menurut Ibn Khaldun adalah membentuk pribadi Muslim yang berbakat, baik bakat intelektual maupun bakat kepribadian (moral/akhlak). Selain itu, agar ia cakap dalam kehidupan pendidikan Islam juga harus punya tujuan pragmatis, yaitu memberikan keahlian (skill) yang relevan dengan tuntutan zaman. Dengan bakat-bakat tersebut seseorang akan dapat mewujudkan peradaban (‘umran) dunia dan memakmurkannya. Tujuan demikian merupakan selaras dengan fungsi penciptaan manusia sebagai khalifah di bumi. Ketika setiap manusia mampu menjadi khalifah dalam pengertian yang sebenarnya, ia akan menjadi rahmat bagi alam semesta (rahmatan lil ‘í¢lamí®n) sebagaimana peran Nabi Muhammad SAW sebagai nabi untuk semua umat.